Dampak Supply Chain dalam Menghubungkan Inovasi dan Kinerja Bisnis Kedai Kopi di Kabupaten Aceh Barat - Keumala Fadhiela ND; Safrika Safrika (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Coffee shops in West Aceh Regency have grown rapidly from the city centre and spread to the coast. But in reality, many coffee shops in West Aceh Regency also have low operational performance, so they experience business failure (bankruptcy). Because West Aceh Regency does not cultivate coffee plants, the coffee supply chain in the coffee shop industry depends on the supply of raw materials from other areas. This study aims to identify and evaluate the adaptability and competence of coffee shop business players. This research is crucial because it relates to supply chain strategies that may seize opportunities and adapt to changing market situations. This research topic is relatively new because research that discusses the effect of Supply chain strategies in mediating innovation and business performance in MSMEs is still lacking. Previous research was mainly researched from the perspective of consumers, so this study was reviewed from the perspective of entrepreneurs. This quantitative research with SEM PLS analysis was conducted in West Aceh Regency. The sample size was 60 respondents, namely coffee shop business actors spread across six sub-districts in West Aceh Regency. The findings demonstrated a strong direct correlation between innovation factors and the success of coffee shops in the West Aceh Regency. However, innovation has no indirect impact on business performance when lean supply chain factors are used as a mediator. However, when supply chain mediation is used, there is a sizable indirect impact of innovation on corporate success. Given how competitive the coffee industry is becoming in West Aceh Regency, this research is anticipated to advance knowledge significantly and offer insight into creating supply chain strategies and innovation. Moreover, this study might be used as a guide for future supply chain-related investigations.